Utilization of public oral health services by New South Wales teenagers, 2004–05 to 2014–15. (December 2016) - Skinner, J; Byun, R; Blinkhorn, A
Abstract: Background: The aims of this study were to examine variations in levels of access to public oral health services in New South Wales by teenagers from 2004–05 to 2014–15 and to determine whether more teenagers have been treated with preventive dental items in keeping with the strategic shift statewide towards prevention and early intervention. Methods: This study involved an analysis of a subset of the New South Wales Oral Health Data Collection for teenagers treated in the New South Wales Public Oral Health Service in the financial years 2004–05 to 2014–15. Relevant Australian Dental Association dental service item groups are reported for teenagers by year as a percentage of total visits delivered in that year. Results: The utilization of the New South Wales Public Oral Health Service by teenagers has remained relatively stable over the 11 years at approximately 6%, while the provision of some preventive items increased over the time period. Conclusions: There were important differences found in access by teenagers to preventive items by socio‐economic status and rurality, and these differences will be targeted over the coming years by New South Wales Public Oral Health Services and better monitored by a new electronic oral health record being implemented statewide from 2016.